DAYA BUNUH INSEKTISIDA MALATHION DAN CYNOFF 25 ULV TERHADAP NYAMUK Aedes aegypti DI KABUPATEN PEKALONGAN - sudaryanto .; M. Choeroel Anwar; Yuni Arti (Pena Medika Jurnal Kesehatan, 2010)
Background: Aedes aegypti mosquito is a kind of vector of Dengue Hemoragic Fever. The insecticide kind of organophosphate and pyrethroid sintetic was used to vector control. This research purposed to know kill off ability malation insecticide and cynoff 25 ULV appear Aedes aegypti mosquito.Methods: entomology test method was used bio assay test with steamed as per standard Health Departement of Indonesia requirement.Result: the result shown that kill off ability malation insecticide most efective reached die 100% were used consentration 6% and for cynoff 25 ULV most effective with consentration 7%.Keywords : kill off abilit,  malation insecticide and cynoff 25 ULV, Aedes aegypti